Pengaruh Health Education terhadap Perilaku Personal Higiene pada Murid Sekolah Dasar yang Mengalami Kecacingan di SD Insp Pampang I Kota Makassar - Sunarti, Sunarti (Window of Health : Jurnal Kesehatan, 2018)
Health problems that are still considered trivial and less attention is the problem of worms. The prevalence of worms in Indonesia reached 28.12%. This is influenced by a lack of knowledge about the importance of clean and healthy living behavior (PHBS) which includes knowledge of personal hygiene. The purpose of this study is To assess the effect of health education on the behavior of Personal Hygiene In Primary School Students Who Were Experiencing Wear at Pampang I Inpres I Makassar City. The research design used is pre experimental approach with one group pre and post test design with sampling technique that is total sampling, total sample is 146 samples, the result of this research is presented in the form of narration and table. Data were analyzed using T test statistic test with significance level Î± = 0, 005. The result showed that there was a significant change of personal hygiene knowledge before and after health education with significant value Ï = 0.001, no significant change in personal hygiene attitude before and after health education given the value of Ï = 1, 818, but there is still a positive attitude increase that is before the positive attitude intervention of 18.8% increased to 71.3% after intervention and there is a meaningful change in personal hygiene before and after given health education with value Ï = 0.001. There is a change in personal hygiene behavior from before and after health education given 71.25% to be better behavior. This research became a reference and learning materials for nursing students, especially nursing and nursing epidemiology.